2022
DOI: 10.18488/35.v9i4.3226
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Board Independence, Gender Diversity and Board Size on Firm Performance in Malaysia

Abstract: The aim of this research is to investigate the effects of corporate governance characteristics on a company’s financial performance. To this end, board independence, board gender composition and board size were tested to determine whether they have any influence on a firm’s financial performance. Given the high concentration of ownership in listed companies in Malaysia and the prevalence of family ownership, this research provides evidence from an emerging market. The Malaysian Code on Corporate Governance (MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Beasley (1996) explained that independent directors hold better judgment and fair representation of shareholders' interest, suitability as a reliable governing mechanism and their potential ability to concentrate on ensuring the maximization of shareholder value. In the study conducted by Nahar et al (2022) board independence and board gender diversity support the initiatives taken by the Securities Commission. Hence, increasing the number of independent directors to make up at least half of the board size is important in enhancing board independence.…”
Section: Board Independence and Financial Distressmentioning
confidence: 94%
“…Beasley (1996) explained that independent directors hold better judgment and fair representation of shareholders' interest, suitability as a reliable governing mechanism and their potential ability to concentrate on ensuring the maximization of shareholder value. In the study conducted by Nahar et al (2022) board independence and board gender diversity support the initiatives taken by the Securities Commission. Hence, increasing the number of independent directors to make up at least half of the board size is important in enhancing board independence.…”
Section: Board Independence and Financial Distressmentioning
confidence: 94%
“…Furthermore, from the review of empirical reviews, it was found that there is an inconsistent result among the links between CG and FP. Some studies revealed a positive relation (Nahar et al, 2022) conducted in Malaysia by selecting of 70 sample of non-financial firms from 2016 to 2020. Detthamrong et al (2017) noted that board size insignificantly and negatively influenced the FP in Thailand, some of the studies indicating a negative effect.…”
Section: Corporate Governance and Firm Performance -Direct Effect Per...mentioning
confidence: 99%
“…The board's size in a company has a significant influence in reducing company costs and maximizing company performance outcomes (Abdullah et al, 2022). According to Rahman et al (2022), a small board size can produce effective communication and coordination, and it significantly affects company performance.…”
Section: Introductionmentioning
confidence: 99%